Thermodynamics and performance of the Mg–H–F system for thermochemical energy storage applications. Issue 4 (5th January 2018) - Tortoza, Mariana S.; Humphries, Terry D.; Sheppard, Drew A.; Paskevicius, Mark; Rowles, Matthew R.; Sofianos, M. Veronica; Aguey-Zinsou, Kondo-Francois; Buckley, Craig E.
Abstract : Fluorine substitution for hydrogen in MgH2 increases overall thermodynamic stability producing viable materials for thermal energy storage applications. Abstract : Magnesium hydride (MgH2 ) is a hydrogen storage material that operates at temperatures above 300 °C. Unfortunately, magnesium sintering occurs above 420 °C, inhibiting its application as a thermal energy storage material. In this study, the substitution of fluorine for hydrogen in MgH2 to form a range of Mg(H x F1− x )2 ( x = 1, 0.95, 0.85, 0.70, 0.50, 0) composites has been utilised to thermodynamically stabilise the material, so it can be used as a thermochemical energy storage material that can replace molten salts in concentrating solar thermal plants. These materials have been studied by in situ synchrotron X-ray diffraction, differential scanning calorimetry, thermogravimetric analysis, temperature-programmed-desorption mass spectrometry and Pressure–Composition–Isothermal (PCI) analysis. Thermal analysis has determined that the thermal stability of Mg–H–F solid solutions increases proportionally with fluorine content, with Mg(H0.85 F0.15 )2 having a maximum rate of H2 desorption at 434 °C, with a practical hydrogen capacity of 4.6 ± 0.2 wt% H2 (theoretical 5.4 wt% H2 ). An extremely stable Mg(H0.43 F0.57 )2 phase is formed upon the decomposition of each Mg–H–F composition of which the remaining H2 is not released until above 505 °C. PCI measurements of Mg(H0.85 F0.15 )2 have determined the enthalpy (Δ H des ) to be 73.6 ± 0.2 kJ mol −1 H2 and entropy (Δ S des ) to be 131.2 ± 0.2 J K −1 mol −1 H2, which is slightly lower than MgH2 with Δ H des of 74.06 kJ mol −1 H2 and Δ S des = 133.4 J K −1 mol −1 H2 . Cycling studies of Mg(H0.85 F0.15 )2 over six absorption/desorption cycles between 425 and 480 °C show an increased usable cycling temperature of ∼80 °C compared to bulk MgH2, increasing the thermal operating temperatures for technological applications.